Comatose patient with hypothermia, dyspnea, and general edema in the emergency department: a case report. Issue 10 (October 2018) - Tsai, Shang-Li; Lin, Chi-Chun; Lin, Cheng-Yu; Keng-Wei, Chang; Chien, Cheng-Yu
Patients presenting to the emergency department with hypothermia are rare and often require prompt diagnosis and management. Myxedema coma, which may cause severe hypothermia, is a true endocrine emergency requiring early and appropriate treatment. We report on a 47-year-old woman with a history of hyperthyroidism who underwent thyroidectomy 5 years previously, with no regular medication or examinations. She presented to the emergency department with a 1-month history of progressive dyspnea associated with general weakness. She also showed hypothermia, decreased mental status, and general edema. Echocardiography revealed increased pericardial effusion without tamponade. Laboratory examination suggested myxedema coma and hypothyroidism. She received thyroxine, glucocorticoid supplement, and intensive supportive care, after which she gradually improved and was discharged. This case suggests that myxedema coma should be considered in patients with hypothyroidism or a history of thyroidectomy who present with change in consciousness, hypothermia, or other symptoms related to critical or slow presentation in multiple organs. Moreover, long-standing hypothyroidism or precipitating acute events such as sepsis, cerebrovascular accidents, gastrointestinal bleeding, cold exposure, trauma, and some medications may also cause myxedema coma. Myxedema coma is associated with a high mortality, and patients suspected to be suffering from this condition should be treated without delay.